Endopyelotomy with Acucise for secondary ureteropelvic junction obstruction report of a case - Umekawa, T (Hinyokika kiyo. Acta urologica Japonica, 1998)
We report a case of successful endopyelotomy using the Acucise cutting balloon device for secondary ureteropelvic junction obstruction (UPJO). A 23-year-old man was hospitalized with the chief complaint of left lumbago and left hydronephrosis due to left UPJO. He underwent antegrade endopyelotomy with a nephroscope and open pyeloplasty. However, left lumbago and hydronephrosis did not show improvement. Acucise endopyelotomy was performed under epidural anesthesia. The operative time was 55 minutes and the hospital stay after the operation was 4 days. There were no operative complications and 3 months later, the operative results were satisfactory as determined by drip infusion pyelography and the disappearance of the lumbago